BOOK BRANDING AND PROMOTING AUTHORIAL IDENTITY: A COMPARATIVE APPROACH - CULEA, MIHAELA (Knygotyra, 2012)
Marketing books discuss personality branding, institutional branding, corporate branding, product branding, or touristic branding, but books are excluded from the discussion on product brands, even though we witness a growing interest in books and writers as cultural products. More than that, we may say that the book is a commodity in the context of the consumer revolution and “the commoditization of knowledge”, to use Roberta Sassatelli’s phrase [31]. If nations, towns, universities, business schools, celebrities, even TV programmes are brands, then books could be considered as brands, too. We could even say that books are commodified brands and the branding process must involve efficient branding strategies, so authors construct a brand as a marker of their identity in the postmodern commodified world.The paper looks at some current strategies for book and authorial branding, which were theoretically launched by American authors, and the ways in which they are practised by English and Romanian authors. Firstly, we provide the aims and scope of the study and the conceptual framework assisting us in the discussion of current trends in book branding, and we also expound the trajectory from classical brand types to books as brands. Secondly, we present the major features of the book branding process and illustrate some book and authorial branding strategies and the extent of their usage in England and Romania, such as self-publishing, the digitalization of the writer, the commodification of arts or the pact between art and business, which instantiates this phenomenon. The results of the comparative exploration of these branding strategies disclose the various differences between Romanian and English literary production, management and marketing practices that enable books and their authors to respond to the new cultural and commercial demands.The investigation takes its cue from aspects concerning literary production, modern publishing and print culture, marketing discourse and practices, cultural production, and cultural studies in general.
Keywords: book; cultural marketing; book branding; branding strategies; authorial identity; self-publishing